2014
DOI: 10.1093/emph/eou018
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic tree shapes resolve disease transmission patterns

Abstract: The shapes of phylogenies of pathogens can reveal patterns in how an outbreak spreads. We used simple features to summarise the shapes of pathogen phylogenies. This provided enough information to distinguish outbreaks with super-spreaders, outbreaks spreading homogeneously, and those with chains of transmission.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 38 publications
1
81
0
Order By: Relevance
“…Moreover, the geographic cluster from Bajardi and colleagues fully overlap the limited geographic distribution of BVDV-1f samples reported by our phylogeographic analysis for the recent years. According to the topology of both the phylogenetic tree and the transmission network, the introduction of BVDV-1f into Aosta Valley occurred like an outbreak, having the structure of a network with a super-spreader (Colijn and Gardy, 2014), with one index case and two distinct ways of infection. Additionally, the relationship inferred by molecular epidemiology among farms clustering in significant subclades (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the geographic cluster from Bajardi and colleagues fully overlap the limited geographic distribution of BVDV-1f samples reported by our phylogeographic analysis for the recent years. According to the topology of both the phylogenetic tree and the transmission network, the introduction of BVDV-1f into Aosta Valley occurred like an outbreak, having the structure of a network with a super-spreader (Colijn and Gardy, 2014), with one index case and two distinct ways of infection. Additionally, the relationship inferred by molecular epidemiology among farms clustering in significant subclades (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, intra-host and inter-host evolution change the association between transmission and phylogenetic trees. 120 Although Bayesian methods have been developed that jointly estimate transmission and phylogenetic trees and capture within host pathogen dynamics, [117][118][119] in many cases there may be too much uncertainty to resolve person to person transmission networks, even with WGS data. new capacity to provide (near) real time data on the origin and transmission dynamics of pathogens could provide a major public health benefit.…”
Section: Analysis Of the Spread Of Pathogens At Different Scales Realmentioning
confidence: 99%
“…121 A growing body of statistical methods is aimed at inferring transmission networks and contact structures from pathogen genomic data, with and without contextual epidemiological information. [116][117][118][119][120] These methodological developments provide new opportunities for proactive laboratory surveillance and a better understanding of the epidemiology of high burden infectious d iseases. 3 12 65 122 123 For example, examination of the genomic diversity of Salmonella typhimurium in co-located human and animal populations in the UK showed that a large proportion of transmissions occurred between humans, challenging the current belief that human to human transmission is uncommon in the developed world.…”
Section: Pathogen Genome Sequencingmentioning
confidence: 99%
“…However, there are indications that while genomic data alone cannot identify individual transmission events, it can provide some insight into the overall dynamics of the outbreak, including whether or not the outbreak shows evidence of a superspreader (85) and which patients are most central to the outbreak network (80). These patterns can be detected within the first several isolates from an outbreak (85), suggesting that real-time WGS may be useful in understanding an outbreak and its key players, thereby informing the public health approach to managing the situation.…”
Section: Advancing Molecular Epidemiology With Wgsmentioning
confidence: 99%